How family ownership affects firm performance : Evidence from the Korean Exchange - Lieskoski, Kyungmin (My University, 2020)
The main purpose of this study is to find out if family ownership of firms has any effect on firm performance. And if there is an effect, to see if it leads to a positive or negative impact on the performance of a firm. A large share of firms is controlled by families worldwide. Korea is well known as a country that has a high percentage of family-owned firms. South Korea also has special ownership structures for firms, including the large conglomerates known as Chaebol, of which most are family-owned. As previous studies of Korean firms tend to focus on the Chaebols, this study instead focuses on smaller firms listed on the Korean Exchange. Data is collected for 307 non-financial companies that were continuously listed on the KOSPI SmallCap index during the years 2013-2017, giving 5 years of balanced data. The measures used to assess firm performance were both a market measure (Tobin’s Q) and accounting measures (ROE and two measures of ROA). Firms were defined as family-owned if any of three conditions were satisfied: if the CEO or a family member of the CEO is a board member, or if the CEO and/or the family members own more than 20% of the firm’s equity, or if the current CEO is a family mem-ber of the previous CEO or the founder of the firm. So far, many previous studies have shown that family ownership will solve the issue of the agency problem, which leads to the result that family-owned firms outperform non-family firms. In this paper, using pooled OLS regression, the relationship between family ownership and firm performance was examined using Tobin’s Q, ROA and ROE. The regression results show at a significant level that family-owned firms have higher ROE and ROA values than non-family owned firms, while family-owned firms had lower values for Tobin’s Q than non-family owned firms.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance